2020
DOI: 10.18483/ijsci.2378
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ivermectin in SARS-CoV-2/COVID-19 Patients

Abstract: Background:The first case of Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were diagnosed in Wuhan, China in 2019. In the first half of 2020 this disease has already converted into a global pandemic. Objectives: To assess the efficacy of Ivermectin in mild cases of COVID-19 patients on the basis of predefined assessment criteria. Study Settings: Fatima Memorial Hospital, Lahore Study Design: Open label randomized control trial. Duration of Study: From 1 st May, 2020 to 30 th June,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Our search yielded 256 citations with an additional nine citations identified in pre-print web pages; 253 records were excluded. After our assessment of 12 full-texts, we identified 10 RCTs [28][29][30][31][32][33][34][35][36][37] (n=1,173) (Figure 1). Two full-texts were excluded as there was no control group in one study, and an outcome of no interest (duration of fever) was the only one reported in another study.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search yielded 256 citations with an additional nine citations identified in pre-print web pages; 253 records were excluded. After our assessment of 12 full-texts, we identified 10 RCTs [28][29][30][31][32][33][34][35][36][37] (n=1,173) (Figure 1). Two full-texts were excluded as there was no control group in one study, and an outcome of no interest (duration of fever) was the only one reported in another study.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…All patients had positive RT-PCR for SARS-CoV-2 at baseline, except in 2 RCTs: Niaee et al [30] had 71% of positivity, and Ravikirti et al [37] had positive RT-PCR or rapid antigen test for SARS-CoV-2. The RCTs by Chachar et al [28], Chaccour et al [34], and López-Medina et al [36] were conducted in non-hospitalized patients. Mean/median age ranged from 26 to 56 years-old, the percentage of female patients ranged from 15% [35] to 78% [36], and most of patients did not have hypertension, diabetes or cardiovascular disease.…”
Section: Characteristics Of Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Several smaller RCTs have reported no benefit with ivermectin. 30, 31, 32, 33 A trial of 585 patients concluded that combined with azithromycin, the use of nitazoxanide, ivermectin, and hydroxychloroquine led to similar clinical outcomes which were better than those in a retrospective control group of patients who had not received any of these three drugs. 34…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, one study conducted in Pakistan that comprised of 50 patients in total (equally divided into case group and control group where both groups received symptomatic treatments but ivermectin was only prescribed to case group) failed to demonstrate any statistically significant outcomes against COVID-19 infection and suggested that symptomatic treatments can be equally effective with or without ivermectin ( Chachar et al, 2020 ). In another study, conducted among 62 mild to moderate SARS-CoV-2 infected patients, ivermectin again failed to demonstrate significant beneficial effects.…”
Section: Introductionmentioning
confidence: 99%